Hydrological Responses to Rainfall Across Varying Canopy Densities in a Tropical Peat Swamp Forest - Lion, Marryanna; Mohti, Azian; Mohd Husin, Hyrul Izwan; Faidi, Mohd Azahari; Misman, Mohd Afizzul; Ismail, Muhammad Nazhif; Sabri, Mohamad Danial Md (Jurnal Manajemen Hutan Tropika, 2025)
Peat swamp forests play a vital role in carbon storage, water regulation, and biodiversity conservation. This study about the hydrological behaviour of three compartments in the Resak Tambahan Forest Reserve with different forest canopy densities categorized as degraded forest and good forest based. Groundwater levels (GWL) and rainfall data were collected and analyzed from April 2023 to June 2024 to evaluate the impact of forest conditions on water retention and hydrological stability. The results show distinct patterns in GWL fluctuations across forest types, with high forest cover density consistently maintaining higher water retention during wet months due to its dense vegetation. A moderate relationship exists between rainfall and GWL variability in all compartments of a healthy forest, with 51% to 65% of the variation in GWL attributed to rainfall amounts. In degraded forest areas, about 52% to 54% of the variation in GWL can also be linked to rainfall effects. Regression analysis revealed a stronger correlation between rainfall and GWL in forests with high canopy density compared to low- and medium-canopy-density forests, suggesting that intact canopy structures enhance predictability in hydrological responses. Conversely, low and medium canopy density forests displayed erratic fluctuations and weaker correlations, highlighting the impact of forest degradation on groundwater dynamics. These findings emphasize the importance of forest canopy density in regulating water cycles and highlight the need for restoration initiatives aimed at improving forest resilience through hydrological studies in degraded peat swamp forests.